Mottness at finite doping and charge instabilities in cuprates - Peli, S.; Conte, S. Dal; Comin, R.; Nembrini, N.; Ronchi, A.; Abrami, P.; Banfi, F.; Ferrini, G.; Brida, D.; Lupi, S.; Fabrizio, M.; Damascelli, A.; et al. (Nature physics, 2017)
The influence of Mott physics on the doping–temperature phase diagram of copper oxides represents a major issue that is the subject of intense theoretical and experimental efforts. Here, we investigate the ultrafast electron dynamics in prototypical single-layer Bi-based cuprates at the energy scale of the O-2 p → Cu-3 d charge-transfer (CT) process. We demonstrate a clear evolution of the CT excitations from incoherent and localized, as in a Mott insulator, to coherent and delocalized, as in a conventional metal. This reorganization of the high-energy degrees of freedom occurs at the critical doping p cr ≈ 0.16 irrespective of the temperature, and it can be well described by dynamical mean-field theory calculations. We argue that the onset of low-temperature charge instabilities is the low-energy manifestation of the underlying Mottness that characterizes the p < p cr region of the phase diagram. This discovery sets a new framework for theories of charge order and low-temperature phases in underdoped copper oxides. The electron dynamics of single-layer Bi 2 Sr 2− x La x CuO 6+ δ is studied as a function of doping, revealing the evolution of charge-transfer excitations from incoherent and localized (as in a Mott insulator) to coherent and delocalized (as in a conventional metal).